1997
DOI: 10.1074/jbc.272.2.1127
|View full text |Cite
|
Sign up to set email alerts
|

An Active Site Substitution, F87V, Converts Cytochrome P450 BM-3 into a Regio- and Stereoselective (14S,15R)-Arachidonic Acid Epoxygenase

Abstract: Cytochrome P450 BM-3 catalyzes the high turnover regio-and stereoselective metabolism of arachidonic and eicosapentaenoic acids. To map structural determinants of productive active site fatty acid binding, we mutated two amino acid residues, arginine 47 and phenylalanine 87, which flank the surface and heme ends of the enzyme's substrate access channel, respectively.Replacement of arginine 47 with glutamic acid resulted in a catalytically inactive mutant. Replacement of arginine 47 with alanine yielded a prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
147
1

Year Published

1997
1997
2005
2005

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(156 citation statements)
references
References 25 publications
(59 reference statements)
8
147
1
Order By: Relevance
“…In order to study further the involvement of Src kinase in endogenous EET signaling, we utilized stable LLCPKcl4 transfectants expressing a regio-and stereoselective 14S,15R-epoxygenase (14S,15R-EET, 99% of total products, 98% optical purity), the enantiomer that predominates in vivo in the kidney (30 -32). This protein is the bacterial cP450 BM3, in which phenylalanine 87 was replaced for valine (F87V BM3) (31) and catalyzes NADPH-dependent arachidonic acid oxidation as a self-contained catalytic unit (31). In the F87V BM3-transfected cells, EGF increased [ 3 H]thymidine incorporation to a significantly greater extent than in cells transfected with the vector alone, and 14,15-EET has been documented to function as an intracellular second messenger in response to EGF (30).…”
Section: Resultsmentioning
confidence: 99%
“…In order to study further the involvement of Src kinase in endogenous EET signaling, we utilized stable LLCPKcl4 transfectants expressing a regio-and stereoselective 14S,15R-epoxygenase (14S,15R-EET, 99% of total products, 98% optical purity), the enantiomer that predominates in vivo in the kidney (30 -32). This protein is the bacterial cP450 BM3, in which phenylalanine 87 was replaced for valine (F87V BM3) (31) and catalyzes NADPH-dependent arachidonic acid oxidation as a self-contained catalytic unit (31). In the F87V BM3-transfected cells, EGF increased [ 3 H]thymidine incorporation to a significantly greater extent than in cells transfected with the vector alone, and 14,15-EET has been documented to function as an intracellular second messenger in response to EGF (30).…”
Section: Resultsmentioning
confidence: 99%
“…The aromatic ring of phenylalanine-87 is close to the haem on the distal side, and it was suggested that this residue could be important in sequestering the terminal methyl of a fatty-acid substrate, thus preventing hydroxylation at this position [3]. We have recently shown that replacement of this residue with an alanine converts the enzyme into a regiospecific ω-hydroxylase for saturated fatty acids [16], while Graham-Lorence et al [17] showed that a phenylalanine to valine mutation at this position similarly increased the regiospecificity of the enzyme towards arachidonic acid, making it a specific (14S,15R)-epoxygenase for this substrate. The only charged residue in the substrate-binding site is arginine-47, which is located at the opening of the substrate access channel, and which has been proposed to be involved in binding the carboxylate group of the substrate.…”
Section: Introductionmentioning
confidence: 99%
“…The crystal structures of the substrate-free [11] and substrate (palmitoleate)-bound [12] forms have allowed the identification of a number of active-site residues likely to interact with substrate or to be otherwise involved in the catalytic process. These include : Arg-47 and Tyr-51, both of which are thought to interact with the carboxylate group of fatty acid substrates [12,14] ; Phe-87, which is known to undergo a dramatic movement on substrate binding and to be vital in the control of the regiospecificity of substrate oxidation [22,23] ; and Phe-42, which is located at the mouth of the long, hydrophobic fatty-acid- Residues Arg-47, Tyr-51 and Phe-42 are located at the ' mouth ' of the hydrophobic channel. Arg-47 and Tyr-51 offer potential interactions with the carboxy group of the fatty acid, and Phe-42 ' caps ' the active site.…”
Section: Introductionmentioning
confidence: 99%